MENGONTROL MORAL HAZARD NASABAH MELALUI INSTRUMEN TA’ZIR DAN TA’WIDH - Wahyudi, Firman (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
Ta'zir and Ta'widh are the two preventive instruments that are born to anticipate moral hazard by the customer against the contract agreement made with the banking. Ta'zir represents a number of penalties stipulated at the start of the contract, definite and designated as a social fund. While Ta'widh in the form of compensation set by the bank, not specified at the beginning of the contract but calculated based on the instantaneous losses experienced by banks and these funds entered as a fee and income bank. Ta'zir provisions get legal legality based on fatwa number 17/DSN-MUI/IX/2000 while Ta'widh based on fatwa number 43/ DSN-MUI/VIII/2004. Both of these instruments aim to discipline customers in order to meet the promised achievements. However, when customers experience a state of overmatch (Force Majoer) these two instruments can not be applied because it is contrary to the principle of Masyaqqat contained in Islamic law.